The Control of HIV After Antiretroviral Medication Pause (CHAMP) Study: Posttreatment Controllers Identified From 14 Clinical Studies. (6th August 2018) - Namazi, Golnaz; Fajnzylber, Jesse M; Aga, Evgenia; Bosch, Ronald J; Acosta, Edward P; Sharaf, Radwa; Hartogensis, Wendy; Jacobson, Jeffrey M; Connick, Elizabeth; Volberding, Paul; Skiest, Daniel; Margolis, David; et al.
Abstract : We identified 67 posttreatment HIV controllers with sustained HIV remission after antiretroviral treatment interruption. Posttreatment control was more commonly identified amongst early treated individuals, frequently characterized by early transient viral rebound and heterogeneous durability of HIV remission. Abstract: Background: HIV posttreatment controllers are rare individuals who start antiretroviral therapy (ART), but maintain HIV suppression after treatment interruption. The frequency of posttreatment control and posttreatment interruption viral dynamics have not been well characterized. Methods: Posttreatment controllers were identified from 14 studies and defined as individuals who underwent treatment interruption with viral loads ≤400 copies/mL at two-thirds or more of time points for ≥24 weeks. Viral load and CD4 + cell dynamics were compared between posttreatment controllers and noncontrollers. Results: Of the 67 posttreatment controllers identified, 38 initiated ART during early HIV infection. Posttreatment controllers were more frequently identified in those treated during early versus chronic infection (13% vs 4%, P < .001). In posttreatment controllers with weekly viral load monitoring, 45% had a peak posttreatment interruption viral load of ≥1000 copies/mL and 33% had a peak viral load ≥10000 copies/mL. Of posttreatment controllers, 55% maintained HIV control for 2 years, with approximately 20% maintaining control for ≥5 years. Conclusions: Posttreatment control was more commonly identified amongst early treated individuals, frequently characterized by early transient viral rebound and heterogeneous durability of HIV remission. These results may provide mechanistic insights and have implications for the design of trials aimed at achieving HIV remission.